Sistem Kendali Dan Pengawasan Wilayah Pintu Berbasis IoT - Arnes Sembiring ((JurTI) Jurnal Teknologi Informasi, 2018)
Abstract - In this study, an IoT-based door security system was proposed which facilitated homeowners to open and close doors and unlock doors through the internet. The system is also equipped with a real time video streaming feature so that the owner can save the environment around the door and ensure the person at the door before opening it. The Raspberry Pi is used as the main controller of the system that provides web pages for users and signatories to access Arduino Uno boards. Arduino Uno controls the servo to control the door. The camera used in this study is a Raspberry Camera with 5 MP resolution. From the results of the tests carried out, the results of the system that have been made can work well. Expected full service and response to changes in users on web pages is also quite fast. Streaming video runs smoothly at 30 fps with a resolution of 640x480.Keywords - Raspberry Pi, Streaming Video, Internet of Things, Door Control